A Resource Based Perspective: Impact of IT Capabilities on Superior Performance Considering the Role of Information Intensity - Shams Eldin, Anwar (The Arab Journal of Administration, 2018)
A company’s resources and capabilities are considered as a sources of superior performance. However, most literature has not clearly linked IT capabilities to superior performance. This paper, therefore, uses the RBV (resource based view) to explore the relationship between company’s IT capabilities and superior performance in Sudanese banking and insurance sectors, through comprehensive model of IT capabilities, which is narrowing define IT capabilities. Moreover, discussing the impacts of an internal factor the information intensity in this relation. Based on a questionnaire collected from IT employees and middle managers the findings of this study indicates that information intensity can be considered as predictor’s factors in the relationship between IT capabilities and superior performance. Moreover, the results show that the different dimensions of IT capabilities have different effects on superior performance. Additionally, the results show how IT capabilities affects the competitiveness of Sudanese’s banking and insurance sectors, and explore the source of advantage. Thus, provided RBV with certain limits, which required for a good theory.